2018
DOI: 10.1108/ribs-05-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Multilatinas: a systematic literature review

Abstract: Purpose The purpose of this paper is to develop a systematic literature review on the subject of multilatinas during 2007-2017, through a review of 55 papers published in 35 journals. Design/methodology/approach A qualitative technique for conducting a systematic literature review was used. To systematize and make the literature review more accurate, it was divided in four stages: data collection, coding, analysis and interpretation of data. Several tables and figures were developed to provide a better inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
0
28
0
1
Order By: Relevance
“…To reply to the RQ of this paper (reference to the pioneering strategic approaches to VI and the use of qualitative approaches in finance studies), a review of the literature about VI in the period 2007-2017 was conducted using the SLR method (Tranfield et al , 2003; Macpherson and Holt, 2007; Gligor and Holcomb, 2012; Lopez-Morales, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To reply to the RQ of this paper (reference to the pioneering strategic approaches to VI and the use of qualitative approaches in finance studies), a review of the literature about VI in the period 2007-2017 was conducted using the SLR method (Tranfield et al , 2003; Macpherson and Holt, 2007; Gligor and Holcomb, 2012; Lopez-Morales, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows that Latin America in the last 20 years has presented an important economic dynamism (L opez-Morales, 2018). The region has registered an upward trend in its Gross Domestic Product (GDP) during the 1998-2018 period.…”
Section: The Ports In Latin Americamentioning
confidence: 99%
“…For example, Bhattacharyya (2020) developed an integrated conceptual framework for international business. Lopez-Morales (2018) made an attempt to find the gaps in the existing literature during the period 2007–2017 in the Latin American context and found that studies in this subject area have increased, although it is still an understudied area. Also, Yang et al (2006) reviewed papers to identify methodologies used in the area of EC; nevertheless, their review was limited to only six journals.…”
Section: Introductionmentioning
confidence: 99%